The Cognitive Perspective in Entrepreneurship: An Agenda for Future Research - Grégoire, Denis A.; Corbett, Andrew C.; McMullen, Jeffery S. (Journal of Management Studies, 2011)
abstractDespite its many achievements, scholarship at the intersection of entrepreneurship and cognition has focused primarily on the consequences of what happens when an entrepreneur benefits from various cognitive characteristics, resources, or other dispositions. As such, cognitive research in entrepreneurship continues to suffer from narrow theoretical articulations and weak conceptual foundations that lessen its contribution to the managerial sciences. To address these issues, we draw from extant work on the nature and practice of cognitive research to develop a systematic approach to study entrepreneurship cognition. To further articulate this agenda, we assess the state of the field by content‐analysing entrepreneurship cognition articles published between 1976 and 2008. We find that, although it has investigated many relevant variables, research on entrepreneurship cognition has failed to fully articulate key conceptual features of the cognitive perspective. Building on these observations, we propose concrete strategies and research questions to augment the contribution of entrepreneurship cognition research, and advance this research beyond its current focus on ‘cognitive consequences’. In particular, we illustrate the scholarly potential of disentangling the various antecedents of entrepreneurship cognition, of studying the process interactions between cognitive resources and mental representations, and of exploring the operation of entrepreneurship cognition across levels of analysis.